Who Wrote the Encheiridion of Epictetus? - Gavrilov, Alexander (Hyperboreus, 2015)
Some critics (Wirth 1967, Selle 2001) have emphasized the fact that Flavius Arrian, who wrote down, collected and disposed texts stemming from the talks of Epictetus, did work that was more than technical and earned him the right to be mentioned in the title of the Epictetean Discourses and Manual. The modern trend to be meticulously delicate with every contribution to any work has led to the consequence that Arrian is sometimes represented as a co-author or even the author of the Discourses as well as of the Manual of Epictetus (so P. Hadot on the title-page of the Manual). The question discussed in this paper treats the nature of authorship: its main parts consist of a certain content presented in a chosen form and based deeply on personal experience. The registration of all persons involved in the process of cultivating and completing a work makes the object of study a matter of literary history, and it is difﬁcult to communicate this to the public on the title page. In the case of Epictetus the author was a teacher of the old philosophical system that he preached in his own way in the oral form. As a smart literary person conscious of the value of the great Stoic teacher, Arrian became an editor of the Discourses and composer of the Manual (᾽Εγχειρίδιον). Knowing both the Prologue of Simplicius’ Commentary in Enchiridium and of Arrian’s Letter to L. Gellius we should take into account the formulations of Arrian himself, who was already confronted with a problem similar to that discussed in this paper. The author ends with a discussion of how to correctly present Epictetean works on the title page of modern editions.